SOLUCIÓN DE LAS ECUACIONES DINÁMICAS DE LA CUERDA BOSÓNICA - Villegas Silvaa, Fulgencio (2005)
By means of the Dirac's method and the Hamiltonian's formalism the Nambu-Goto Classical theory is analyzed, dynamics equations ofthe Boson string are obtained and solved. Following this methodthe algebra of the flTSt class bonds is computed, that are the generators of the action symmetry of the Bosons strings. The analysis is made as for open strings as for close strings.